Reserve Fund Optimatization Model For Digital Banking Transaction Risk With Extreme Value-at-risk Constraints - Moch Panji Agung Saputra; Diah Chaerani; Sukono; Mazlynda Md Yusuf (MDPI, 2024)
Indexed by WOS